Carbides in High Chromium Cast Irons - Wiengmoon, A. (Naresuan University Engineering Journal, 2014)
High chromium cast irons are widely used as abrasion resistant materials. The mechanical properties and wear resistance of these irons depend on the type, hardness, morphology, distribution, volume fraction and orientation of the eutectic and precipitated carbides within their microstructures and on the nature of the matrix supporting these hard eutectic carbides. This paper is aimed to review the nature and crystallography of eutectic carbides and secondary carbides which are formed during solidification and precipitated during heat treatments of high chromium irons.